How pride works. (1st February 2021) - Sznycer, Daniel; Cohen, Adam Scott
Abstract: Abstract: The emotion of pride appears to be a neurocognitive guidance system to capitalize on opportunities to become more highly valued and respected by others. Whereas the inputs and the outputs of pride are relatively well understood, little is known about how the pride system matches inputs to outputs. How does pride work? Here we evaluate the hypothesis that pride magnitude matches the various outputs it controls to the present activating conditions – the precise degree to which others would value the focal individual if the individual achieved a particular achievement. Operating in this manner would allow the pride system to balance the competing demands of effectiveness and economy, to avoid the dual costs of under-deploying and over-deploying its outputs. To test this hypothesis, we measured people's responses regarding each of 25 socially valued traits. We observed the predicted magnitude matchings. The intensities of the pride feeling and of various motivations of pride (communicating the achievement, demanding better treatment, investing in the valued trait and pursuing new challenges) vary in proportion: (a) to one another; and (b) to the degree to which audiences value each achievement. These patterns of magnitude matching were observed both within and between the USA and India. These findings suggest that pride works cost-effectively, promoting the pursuit of achievements and facilitating the gains from others' valuations that make those achievements worth pursuing.